Effects of Supplementing Corn Silage to Fall-Calving Heifers and Cows Grazing Tall Fescue on Cow Performance - J. Wyatt L. Banks; Jaymelynn K. Farney; Karol E. Fike; Jason M. Warner (Kansas Agricultural Experiment Station Research Reports, 2024)
The objective was to test the effect of fescue cultivars and supplemental feeding of cows grazing fescue pastures on cow performance and pasture management. Primiparous and multiparous Angus-based crossed cows (n = 45) averaging 151 ± 7 d of gestation at turnout, were randomly allocated and stratified to pasture treatment by parity. Each pasture contained 3 cows of different ages, consisting of a young (first-calf heifer), middle-aged (3-5 yrs.), and old (≥ 6 yrs.) cow. Treatment was a 2 by 2 factorial design with two types of pasture (toxin producing or non-toxin producing fescue) and two levels of supplemental feeding (non-supplemented or supplemented at 1% of body weight on a DM basis of corn silage). Toxic fescue pastures consisted of K-31 endophyte infected tall fescue (n = 8) tested at 507 ppm ± 0.82 SEM for ergot alkaloids with a 92.5% infection rate. Non-toxic pastures consisted of novel (MaxQ) and endophyte free varieties (n = 7). Cows were fed silage (32-42% DM and 7.83% CP) daily in fence-line bunks, with feeding amount being adjusted at each weigh date. Cows were weighed on 2 consecutive days prior to turnout (middle of the second trimester), midpoint (beginning of the third trimester), and at about 2 weeks prior to the estimated calving date for herd. Body weight, body condition score, hair score, and rump fat measurements were taken at each weigh date. Supplementation tended (P = 0.07) to increase body weight gain and rump fat (P = 0.06) regardless of fescue type. Cattle grazing toxic fescue tended to have longer hair (P = 0.09) and did not “slick” off as quickly as those that were supplemented (P = 0.08). Cattle grazing toxic fescue exhibited classic fescue toxicosis symptoms, and supplementation improved cow performance regardless of fescue cultivar.
Keywords: fescue; toxicity; cows